PERAN ORANG TUA DALAM MEMBENTUK KEPRIBADIAN ANAK USIA 4-5 TAHUN - Nadilla Septria; Rika Juriyanti (Jurnal Al Athfaal, 2023)
This journal explores the pivotal role parents play in shaping the personalities of children aged 4-5 years. Through a synthesis of recent research, it focuses on the impact of parental interactions on the development of a child's personality during this critical stage. Employing qualitative approaches, surveys involving various parents, and observations of parent-child interactions, the study aims to pinpoint specific strategies employed by parents to nurture key aspects of personality during this developmental phase. The comprehensive analysis encompasses diverse parenting methods influencing a child's cognitive patterns, behaviors, and emotional responses. Moreover, this journal underscores the significance of effective parental role modeling in fostering self-confidence, independence, and social skills in preschool-aged children. Within this effort, the correlation between the quality of parental interactions and the characteristics of a child's personality takes center stage. Additionally, the article discusses practical strategies for parents to enhance emotional bonds, support positive development, and establish a robust foundation for a child's personality development. The findings provide profound insights into the vital role of parents in shaping the personalities of 4-5-year-old children, offering practical implications for fostering nurturing parenting styles that support optimal growth.